Vegetation history of the Río Manso Superior catchment area, Northern Patagonia (Argentina), since the last deglaciation - Bianchi, Maria Martha (2012)
In Northern Patagonia, the long-term vegetation-climate relationships that gave shape to southern South American forests have been the subject of extensive investigations in the Andean regions of Argentina and Chile for about a century. The Río Manso Superior originates in one of the tongues of the Cerro Tronador Glacier, near the international border, discharging into the Pacific Ocean after feeding present Lago Mascardi and flowing east to west on a mountain landscape. Ongoing pollen studies in this watershed provide us with a modern analogue to better understand the vegetation history of the region. A pollen record from a 15 m long sediment core retrieved from Lago Mascardi (41°08°S, 71°34°W) contains continuous evidence of vegetation changes in the Río Manso watershed extending back to the last deglaciation. High Andean steppe vegetation with forest patches, and extended waterlogged areas gave place to a forest, probably deciduous, during the Lateglacial-Holocene transition. A forest diversification took place during the climate amelioration that encompassed the deglaciation whilst the vegetation became more open before the onset of the Huelmo-Mascardi cold reversal. A mixed Nothofagus-Austrocedrus forest expanded during the middle Holocene. This forest became denser under the higher climate variability registered in the region during the late Holocene as shown by independent published data. Statistical analyses of modern pollen samples along an altitudinal transect from low Nothofagus forest and shrubland to high Andean semi-desert support this interpretation. Pollen results are discussed in the context of paleoenvironmental reconstructions at a regional scale.